2014
DOI: 10.4322/jms.ao062513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coffee (Coffea arabica) consumption on the femoral morphology and biomechanics in rats

Abstract: Introduction: Coffee consumption has proved to be harmful to osseous tissue integrity, thus, diminishing bone resistance. Considering the great number of individuals consuming coffee daily, therefore, the present study aims to demonstrate the effects of coffee on the femoral morphology and biomechanics resistance in Wistar rats. Methods: Twenty male Wistar rats were chosen for the experiment, divided into two groups (n = 10), as to know, CT (control) group, to which was offered water diet ad libitum; and, CF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…A study in rats observed negative interference of coffee consumption on the material and structural bone properties, diminishes trabecular and cortical bone density, and hence making bones more fragile and likely to fractures. 8 Human physiological studies and controlled balance studies show a clear but only a very small depressant effect of caffeine on intestinal calcium absorption, and no effect on total 24-h urinary calcium excretion. 9 The epidemiologic studies showing a negative effect may be explained in part by an inverse relationship between consumption of milk and caffeine-containing beverages.…”
Section: Discussionmentioning
confidence: 99%
“…A study in rats observed negative interference of coffee consumption on the material and structural bone properties, diminishes trabecular and cortical bone density, and hence making bones more fragile and likely to fractures. 8 Human physiological studies and controlled balance studies show a clear but only a very small depressant effect of caffeine on intestinal calcium absorption, and no effect on total 24-h urinary calcium excretion. 9 The epidemiologic studies showing a negative effect may be explained in part by an inverse relationship between consumption of milk and caffeine-containing beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil dari penelitian ini menunjukkan bahwa konsumsi kopi robusta dapat menurunkan kekuatan tulang. Hasil tersebut sesuai dengan penelitian serupa yang pernah dilakukan mengenai efek konsumsi kopi (Coffea arabica) terhadap biomekanika tulang femur pada tikus yang diberi konsumsi kopi selama 60 hari [6]. Penelitian tersebut membuktikan bahwa biomekanika pada sifat mekanis tulang femur dengan pengujian Three Point Bending Test pada kelompok perlakuan yang diberi konsumsi kopi arabika secara signifikan lebih rapuh dibandingkan dengan kontrol.…”
Section: Pembahasanunclassified
“…Biomekanika terbagi menjadi 2 yaitu struktur mekanis tulang (ukuran, volume, arsitektur tulang) dan sifat mekanis tulang (sel, matriks organik, matriks anorganik tulang) [6]. Hal tersebut sesuai dengan hasil uji Anova dalam penelitian ini yang menunjukkan bahwa tidak terdapat perbedaan yang signifikan pada penimbangan berat badan (BB) tikus minggu 1, minggu 2, d a n minggu 3, s e r t a p a d a penimbangan massa sampel tulang dan luas permukaan sampel tulang femur tikus wistar jantan.…”
Section: Pembahasanunclassified
“…Intakes of caffeine in amounts >300 mg/dl led to low mineralization of the bone organic matrix present in the rat femur (Rapuri et al, 2001). Coffee consumption interferes negatively with bone material and structural qualities and decreases femur trabecular and cortical bone volume (Santos et al, 2018). On the other hand, Sakamoto et al, (2001) found through analyses of bone histomorphometry and serum and urinary biomarkers of bone turnover that coffee consumption did not lead to bone resorption in normal conditions.…”
Section: Introductionmentioning
confidence: 99%